(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
Electrical discharge machining (EDM), is well known process for making complex geometry in plastic injection moulding dies such as AISI P20. The machining parameters like current, voltage, pulse on time, pulse off time, gas supply pressure etc., are influencing the output responses like Material Removal Rate(MRR), Tool Wear Ratio(TWR) and surface quality. Among them pulse on time and current are the major parameter which alters the performance characteristics. The surface textures by different process like knurling, laser texturing and water-jet texturing etc are commonly available and practiced. Sometimes, it is difficult to control surface texture produced on the component. In EDM process, it is possible easily to control the surface texture produced on the component precisely by varying the different process parameters. In the present investigation it is planned to produce the variety of surface textures using EDM technique by varying separately current and pulse on time alone. Copper electrode of diameter 10mm and the work piece AISI P20 tool die steel is selected for machining. Dielectric media used for machining the process is EDM oil. The process is done in two stages. In first stage is done by varying the pulse on time and keeping rest of the parameters constant. The second stage is done by varying current and keeping rest of the parameters constant. The effect of variation in pulse on time and current are completely analysed on the performance characteristics viz. Material Removal Rate (MRR), and surface finish. The microstructural study using optical microscope and SEM with EDS are studied.